The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0073-47212008000100001
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre os sincrânios de Otaria byronia e Arctocephalus australis (Pinnipedia, Otariidae)

Abstract: Iheringia, Sér. Zool., Porto Alegre, 98(1):5-16, 30 de março de 2008 Estudo comparativo entre os sincrânios de Otaria byronia e... Estudo comparativo entre os sincrânios de Otaria byronia eArctocephalus australis (Pinnipedia, Otariidae) ABSTRACT. Comparative study between the syncranium of Otaria byronia and Arctocephalus australis (Pinnipedia, Otariidae). A high degree of anatomical variability in many structures of Otaria byronia (Blainville, 1820) and Arctocephalus australis (Zimmerman, 1783) was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…This confirms the necessity for more extensive and detailed studies of South American species, including large sample sizes, as recommended by Berta and Churchill (2012). Sanfelice and Ferigolo (2008) emphasized the high variability of skull characters in O. byronia and A. australis, refuting many character states previously used in the phylogenetic analysis of pinnipeds. In this context, these authors concluded that a comparative osteological study of all other otariids will certainly be very useful to the solution this problem and to the revision of the characters.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This confirms the necessity for more extensive and detailed studies of South American species, including large sample sizes, as recommended by Berta and Churchill (2012). Sanfelice and Ferigolo (2008) emphasized the high variability of skull characters in O. byronia and A. australis, refuting many character states previously used in the phylogenetic analysis of pinnipeds. In this context, these authors concluded that a comparative osteological study of all other otariids will certainly be very useful to the solution this problem and to the revision of the characters.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, there is limited knowledge about the anatomy of several species (examples of skull descriptions in HOWELL, 1929;SIVERTSEN, 1954;REPENNING et al, 1971;KING, 1983;ANDREESCU;MURARIU, 1985;KASTELEIN;GERRITS, 1990;FERIGOLO, 1996a;MIZUNO;OHTAISHI, 2002;SANFELICE;FERIGOLO, 2008), and the frequent variability in the cranial (NOJIMA, 1990), postcranial (ROBINETTE;STAINS, 1970;ENGLISH, 1977) and dental (DREHMER; FERIGOLO, 1996b;DREHMER et al, 2004;CRUWYS;FRIDAY, 2006;LOCH et al, 2010) character states, which makes it even more difficult to clarify the relationships of this group.…”
Section: Introductionmentioning
confidence: 99%
“…The first study that used the CSA method to estimate the age categories for the pinnipeds found dead in southern Brazil, was Simões-Lopes et al (1995), but they did not compare this with the specimens' GLGs. For the same geographic area several studies were carried out, but over an increased sample; Drehmer & Ferigolo (1996) applied this technique for A. australis skull description; Drehmer & Ferigolo (1997) in a comparative analysis including A. australis and A. tropicalis and Sanfelice & Ferigolo (2008) for A. australis and Otaria flavescens . The CSA method had also been used for several decades in humans in forensic medicine (Meindl & Lovejoy, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The marginal process (sensu Davis, 1964; = secondary angular process in Sanfelice and Ferigolo, 2008) is strongly projected dorsally, and its posterior border has a triangular shape. A well-developed marginal process is also present in Odobenidae (Deméré, 1994); nevertheless, it is useful to discriminate among otariids because in Arctocephalus it is barely patent, whereas in Otaria it is well developed (Sanfelice and Ferigolo, 2008). Therefore, the presence of a well-developed marginal process and the presence of a sinuous ventral margin of the horizontal ramus allows us to identify this specimen as Otaria.…”
Section: Descriptionmentioning
confidence: 99%